The Role of Government Politics and Law in Building Public Participation in Elections - Appe Hutauruk (Syntax Corporation Indonesia, 2023)
The use of voting rights in a general election is the subjective right of citizens (people) who have qualified to vote, but from the aspect of the interests of the state and nation, it can be considered that the use of voting rights / voting rights of citizens in general elections, in essence is a form of responsibility to participate in the administration of government. However, at the current level of reality there is a tendency for people to experience